The Acquisition of Technology and Small Firms by Large Firms - Ove Granstrand; Sören Sjölander (The Research Institute of Industrial Economics (IUI), 1990)
This paper describes how large, typically multi-technology corporations build up and exploit their technological capability by purchasing small, technology-based firms in order to acquire their technology. The frequency, possible causes and economic effects of this phenomenon are elaborated, based on empirical studies of Swedish industry. A new mechanism for trading technology through the trading of small firms among large firms is proposed.
Keywords: D83; G34; O32; 330; Acquisitions; technological progress